(untitled) (Research, Society and Development, 2024)
Introduction: Effective management of epileptic seizures in the emergency setting is vital to ensure patient safety. Epileptic seizures, common neurological events, require rapid interventions to prevent serious complications. The literature emphasizes the importance of well-defined protocols and continuous training of healthcare professionals. Objective: This article provides a comprehensive overview of the multifaceted strategies in managing epileptic seizures in emergency situations, reviewing both pharmacological and non-pharmacological interventions, and highlighting the importance of a combined and comprehensive approach. Methodology: This study conducted a narrative review of the literature on the management of epileptic seizures in the emergency department, using databases such as PubMed and Scopus, covering publications from 2010 to 2023. Studies addressing efficacy, challenges, and protocols in seizure management in emergencies were included. Results: The results indicate that initial protocols are crucial for stabilizing patients. Benzodiazepines, such as lorazepam, are effective in stopping seizures. Complementary exams, such as computed tomography and electroencephalogram, are essential for differential diagnosis. Continuous education of professionals improves competence in managing seizures, and telemedicine can provide real-time specialized support. Discussion: The discussion highlights that well-defined protocols reduce variability in clinical practices and improve patient outcomes. The choice of medication should consider patient characteristics. Differential diagnosis is essential to ensure appropriate treatment. Continuous education and the integration of technologies, such as telemedicine, are fundamental for effective management. Conclusion: It is concluded that proper management of epileptic seizures involves standardized protocols, use of effective medications, complementary exams, and continuous education of professionals. The integration of technologies can improve care coordination. Ongoing research is essential to identify best practices and develop new strategies.